2003
DOI: 10.1162/089892903321593153
|View full text |Cite
|
Sign up to set email alerts
|

Adult Brain Plasticity Elicited by Anomia Treatment

Abstract: Abstract& We describe a study where a specific treatment method for word-finding difficulty (so-called contextual priming technique, which combines massive repetition priming with semantic priming) was applied with three chronic left hemispheredamaged aphasics. Both before and after treatment, which focused on naming of a series of pictures, naming-related brain activity was measured by magnetoencephalography (MEG). Due to its excellent temporal resolution and good spatial resolution, we were able to track tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
100
1
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(115 citation statements)
references
References 70 publications
(97 reference statements)
9
100
1
5
Order By: Relevance
“…starting ~300ms after picture presentation, were observed, on the other hand, in aphasic speakers with predominantly lexical-phonological Time-course of phonetic encoding 6 encoding impairments (Laganaro et al, 2009. Similar results were reported in a MEG study on recovery from anomia in patients with lexical-phonological impairments (Cornelissen et al, 2003). Here, MEG changes between pre-and post-treatment assessments were observed starting at 300ms after picture presentation.…”
Section: Time Course Of Speech Encoding Processessupporting
confidence: 86%
See 3 more Smart Citations
“…starting ~300ms after picture presentation, were observed, on the other hand, in aphasic speakers with predominantly lexical-phonological Time-course of phonetic encoding 6 encoding impairments (Laganaro et al, 2009. Similar results were reported in a MEG study on recovery from anomia in patients with lexical-phonological impairments (Cornelissen et al, 2003). Here, MEG changes between pre-and post-treatment assessments were observed starting at 300ms after picture presentation.…”
Section: Time Course Of Speech Encoding Processessupporting
confidence: 86%
“…between 100-250ms after stimulus onset) or lexical-phonological impairments (i.e. from 300ms after stimulus onset ;Cornelissen et al, 2003;Laganaro et al, 2008;2009;2011). In previous studies, the atypical ERPs observed in sub-groups of anomic patients converged with the dynamics of encoding processes estimated in healthy subjects (Indefrey & Levelt, 2004;Indefrey, 2011).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Alternatively, ERP studies on word production have used silent or delayed production paradigms during picture naming (Cornelissen et al, 2003;Jescheniak, Hahne, & Schriefers, 2003;Laganaro, Morand, & Schnider, 2009;Vihla, Laine, & Salmelin, 2006). In these studies participants either prepared the word (producing it overtly after a delay falling beyond the analysed period), or they said the word in their mind, therefore also avoiding possible artefacts during motor preparation and execution.…”
Section: Introductionmentioning
confidence: 99%